Age-based differences in the disability of extremity injuries in pediatric and adult occupants. (25th November 2019) - Gaffley, Michaela; Weaver, Ashley A.; Talton, Jennifer W.; Barnard, Ryan T.; Stitzel, Joel D.; Zonfrillo, Mark R.
Abstract: Objective: The objective was to develop a disability-based metric for motor vehicle crash (MVC) upper and lower extremity injuries and compare functional outcomes between children and adults. Methods: Disability risk (DR) was quantified using Functional Independence Measure (FIM) scores within the National Trauma Data Bank–Research Data System for the top 95% most frequently occurring Abbreviated Injury Scale (AIS) 3 extremity injuries (22 unique injuries). Pediatric (7–18 years), young adult (19–45 years), middle-aged (46–65 years), and older adult (66+ years) MVC occupants with an FIM score and at least one of the 22 extremity injuries were included. DR was calculated for each injury as the proportion of occupants who were disabled of those sustaining the injury. A maximum AIS-adjusted disability risk (DRMAIS ) was also calculated for each injury, excluding occupants with AIS 4+ co-injuries. Results: Locomotion impairment was the most frequent disability type across all ages. DR and DRMAIS of the extremity injuries ranged from 0.06 to 1.00 (6%–100% disability risk). Disability risk increased with age, with DRMAIS increasing from 25.9% ± 8.6% (mean ± SD) in pediatric subjects to 30.4% ± 6.3% in young adults, 39.5% ± 6.6% in middle-aged adults, and 60.5 ± 13.3% in older adults. DRMAIS for upper extremity fractures differed significantly between age groups, with higher disability in older adults, followed by middle-aged adults. DRMAIS for pelvis, hip, shaft, knee, and other lower extremity fractures differed significantly between age groups, with older adult DRMAIS being significantly higher for each fracture type. DRMAIS for hip and lower extremity shaft fractures was also significantly higher in middle-aged occupants compared to pediatric and young adult occupants. The maximum AIS-adjusted mortality risk (MRMAIS, proportion of fatalities among occupants sustaining an MAIS 3 injury) was not correlated with DRMAIS for extremity injuries in pediatric, young adult, middle-aged, and older adult occupants (all R 2 < 0.01). Disability associated with each extremity injury was higher than mortality risk. Conclusions: Older adults had significantly greater disability for MVC extremity injuries. Lower disability rates in children may stem from their increased physiological capacity for bone healing and relative lack of bone disease. The disability metrics developed can supplement AIS and other severity-based metrics by accounting for the age-specific functional implications of MVC extremity injuries.